Fuzzy logic based surface modeling and 3-D blending - Çinar, Ahmet; Arslan, Ahmet (My University, 2002)
In this paper, we propose a method for free form surface modeling based on fuzzy logic technique. The presented method is dependent on finding the control points of surface. The main objective of the method is to construct the surface by modeling the curves when the initial and final points are known. Firstly, each curve is modeled and then a surface is generated by joining the created curves. The method is applied to 3D blending and some blended objects are given.
Bulanik mantik tabanliyüzey modelleme ve üç boyutta nesne kaynaştirma işlemine uygulamasi
Keywords: Blending; Fuzzy logic technique; Surface modeling